A large‐scalable spraying‐spinning process for multifunctional electronic yarns. Issue 2 (27th September 2022) - Gan, Linli; Zeng, Zhen; Lu, Haojie; Li, Daiqi; Wei, Ke; Cai, Guangming; Zhang, Yingying
Abstract: Electronic fibers/textiles have great potential for applications in smart wearables due to their excellent flexibility, air permeability, and wearing comfort. However, it is still challenging to produce reliable electronic textiles at low cost and in a large scale. Herein, we report a spraying‐spinning process for fabricating electronic yarns with excellent stability and durability. Cotton sliver, which is the raw material for spinning conventional cotton yarns, was spray coated with carbon nanotubes (CNTs) and spun on an Ag@nylon yarn, forming a sheath‐core structured CNT@cotton‐Ag@nylon yarn (CCAY). The process is continuous, large‐scalable, applicable to other raw fiber materials and compatible with traditional textile processes. The as‐prepared CCAY showed superior mechanical durability, washability, and conductivity to typical surface coated yarns. It can be easily processed or integrated into textiles through weaving, knitting, sewing, and embroidering. We systematically studied the electromechanical, electro‐thermal, and photothermal performance of CCAY based yarns/fabrics, demonstrating its versatile applications in smart textiles. In addition, CCAY can be further equipped with other features, such as electro‐thermochromic functions, pH sensing and flame resistant abilities. Considering the large‐scalability, versatility, and low‐cost, we foresee that this spraying‐spinning process for electronic yarns may play important roles in the development of practical smart fibers/textiles. Abstract : A continuous, large‐scalable spraying‐spinning process for fabricating reliable and durable multifunctional electronic yarns is reported. The process can be applied with various raw fiber materials and is compatible with traditional textile processes. The as‐prepared yarns show excellent mechanical durability, washability, good conductivity and multiple electronic functions, enabling its versatile applications in smart textiles.